The relationship between the big five personality traits and job performance among employees in public sector in Kuching/ Anie Bilaini Abdol Lachek … [et al.] - Abdol Lachek, Anie Bilaini; Charles, Chrissila; Mohamad Norizam, Nur Ashikin; Sahak, Nur Syazwani (2020)
The job performance of an individual is the function of skills, knowledge, motivation and abilities directed to role prescribed behavior. Understanding the personality of employees that can be see that employee behavior is an advantageous informational data point for management. Recent studies show that leaders’ personality traits also affect job performance in the organization that studies by Ghani (2016). Not every personality is suited for every job position, so it is important to recognize personality traits and pair employees with the duties that fit their personalities the best. McCrae (1987) is the researcher who develop the Big Five Personality traits that described the personality of human like is extraversion, agreeableness, openness, conscientiousness and neuroticism. Conscientiousness refer to the extent to which a person is organized, careful, self-disciplined, and responsible (Seng, 2013). If conscientiousness does not improve job performance but when people are hardworking that can increase job performance. So conscientiousness can make the employee more self-discipline and can organized their work well with their own efforts. Customer service work requires a service provider to become dependably and follow procedure and rules and it suits well the traits of conscientiousness. For instance, customer service occupation positively exhibited a higher level of conscientiousness.